2021
DOI: 10.5435/jaaosglobal-d-21-00107
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcomes of Revision Hip Arthroscopy Irrespective of Whether Index Surgery was Performed by the Same Surgeon or a Different Surgeon

Abstract: Introduction: The purpose of this study was to compare minimum 2-year patient-reported outcomes (PROMs) after revision hip arthroscopy between two different patient cohorts who had undergone primary hip arthroscopy with the same surgeon (SS) and a different surgeon (DS). We hypothesized no difference in clinical outcomes between the groups despite differences in intraoperative findings based on the surgical decision making in a revision setting at a high-volume center. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…If nonoperative modalities do not improve symptoms, then clinicians must decide whether the most appropriate treatment includes a 1 3 revision arthroscopic surgery or an open procedure such as a periacetabular osteotomy (PAO). While studies have demonstrated improved outcomes following revision hip arthroscopy [1,19], a paucity of data exists for patients undergoing a PAO after a failed hip arthroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…If nonoperative modalities do not improve symptoms, then clinicians must decide whether the most appropriate treatment includes a 1 3 revision arthroscopic surgery or an open procedure such as a periacetabular osteotomy (PAO). While studies have demonstrated improved outcomes following revision hip arthroscopy [1,19], a paucity of data exists for patients undergoing a PAO after a failed hip arthroscopy.…”
Section: Introductionmentioning
confidence: 99%